Pengaruh Harga, Kualitas Produk dan Promosi terhadap Keputusan Pembelian Orbit di Telkomsel Kota Sorong - Maria Manda Puspita; Niluh Nyoman Tantri (Journal of Innovative and Creativity, 2025)
This research aims to determine the Effect of Price, Product Quality and Promotion on Orbit Purchasing Decisions in Telkomsel Sorong City. With multiple linear regression analysis techniques. The results of the t-test, the price variable is tcount 1.801> from ttable 1.6616, or the significance value is 0.075 smaller than 0.05. This means, because t-count> t-table, it can be concluded that the hypothesis (H1) is accepted, accepted, The t-count value of product quality is tcount 3.370> from ttable1.6616, or the significance value is 0.001 smaller than 0.05. This means, because t-count> t-table, it can be concluded that the hypothesis (H2) is accepted. The t-count value of promotion is tcount 4.232> from ttable1.6616, or the significance value is 0.000 smaller than 0.05. This means that since the calculated t-value is greater than the calculated t-value, hypothesis (H3) can be concluded as accepted. The calculated F-value is 68.198, with a significance value of 0.000. This test result indicates a significance level of <0.05. This indicates that the variables price, product quality, and promotion simultaneously influence purchasing decisions.